Visual event-related potencial (P300): a normative study - Heloisa Veiga; Andréa Deslandes; Maurício Cagy; Kaleb McDowell; Fernando Pompeu; Roberto Piedade; Pedro Ribeiro (Arquivos de Neuro-Psiquiatria)
The P300 component of the Event-Related Potential (ERP) is a general measurement of "cognitive efficiency". It is an index of the ability of an individual's Central Nervous System (CNS) to process incoming information. OBJECTIVE: To develop a normative database for the visual P300. METHODOLOGY: 30 right-handed individuals (same number of each sex), between 20 and 30 years of age, healthy, free of any cognitive impairment and not making use of psychoactive substances. Participants were submitted to a visual discrimination task, which employed the "oddball" paradigm. RESULTS: The expected scalp distribution trend was seen for latency but not for amplitude values. CONCLUSION: A high variability of latency and amplitude values was observed across the age span. Mean reaction time for the entire sample of the study was 391.56 ± 37.03 ms.